Representation of Food Image in the Poem of Spice Boy: Ari Ambarwati's Work as a Gastronomic Study - Setiawan, Bagas; Ma'arif, Moh Syamsul (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
This study aims to analyze the representation of food images in the poem "Spice Boy" by Ari Ambarwati as a gastronomic study. The main focus of this research is to identify the elements of food presented in poetry and the symbolic meanings contained in them, and how this contributes to the understanding of the cultural identity of Indonesian people. The method used in this study is the analysis of poetry texts with a qualitative approach. The researcher conducted an in-depth reading of the poem "The Spice Boy" to identify the image of the food that emerged, as well as the cultural and social context behind it. In addition, this study also examines gastronomic references contained in poetry, including the use of spices and traditional foods as symbols of identity. The results of the analysis show that this poem is rich in food imagery that is not only appetizing, but also implies deep cultural values. Food in poetry serves as a bridge between generations, connecting past experiences with the present. The spices presented in the poem reflect Indonesia's natural wealth and its important role in people's daily lives. In addition, this poem also highlights the importance of preserving culinary heritage as part of cultural identity. The conclusion of this study is that Ari Ambarwati's "Spice Boy" serves not only as a literary work, but also as a cultural document that reflects on the relationship between food, identity, and collective memory. This research is expected to contribute to a deeper understanding of the relationship between literature and gastronomy, as well as encourage efforts to preserve Indonesia's rich and diverse culinary heritage..